Measurement of Geotextile-Water Characteristic Curves Using a Controlled Outflow Capillary Pressure Cell. Issue 3 (1st January 2001) - Knight, M.A.; Kotha, S.M.
Abstract : The present paper describes the use of a controlled outflow capillary pressure cell for the measurement of geotextile-water characteristic curves. Fine sand with a known soil-water characteristic curve and a geotextile column drainage experiment were used to validate the controlled outflow cell. The controlled outflow cell was also used to measure drainage geotextile-water characteristic curves for one, three, and six vertically stacked nonwoven geotextile specimen layers. Test results indicate the following: (i) the controlled outflow cell can measure a complete nonwoven drainage geotextile-water characteristic curve with a water entry pressure of 50 mm; (ii) vertical stacking of the nonwoven geotextile has little influence on the geotextile-water characteristic curve; and (iii) a geotextile-water characteristic curve can be measured in less time when compared with Klute's method. Test results also indicate that ASTM D 854 may be used to determine the specific gravity of the nonwoven geotextile.